Effect of different metal oxides on the catalytic activity of Î³-Al2O3-MgO supported bifunctional heterogeneous catalyst in biodiesel production from WCO - Farooq, M. (Royal Society of Chemistry, 2016)
The catalytic activity of different Î³-Al2O3-MgO supported bifunctional solid catalysts was successfully evaluated by carrying out simultaneous esterification-transesterification reactions in waste cooking oil. The physicochemical properties of the synthesized catalysts were studied using different characterization techniques to identify a catalyst of proper configuration for proper operation conditions to develop a sustainable and economical biodiesel production process. The results indicated that the Mo-Mn/Î³-Al2O3-15 wt MgO catalyst showed excellent performance in biodiesel production from selected waste cooking oil as compared with Mo-Zn/Î³-Al2O3-15 wt MgO or Mo-Sn/Î³-Al2O3-15 wt MgO catalysts and provided a biodiesel yield of 91.4 under optimal reaction conditions, i.e. methanol/oil molar ratio of 27:1, 5 wt catalyst and a reaction temperature of 100 Â°C for 4 h. The good catalytic activity could be attributed to the existence of the optimal number of catalytically active sites on the surface of the catalyst. Moreover, the catalyst showed substantial reusability in biodiesel production from waste cooking oil. Â© 2016 The Royal Society of Chemistry.